2009
DOI: 10.1073/pnas.0809130106
|View full text |Cite
|
Sign up to set email alerts
|

RE-1–silencing transcription factor shows tumor-suppressor functions and negatively regulates the oncogenic TAC1 in breast cancer cells

Abstract: Breast cancer remains the most prevalent cancer among women in the United States. Substance P, a peptide derived from the TAC1 gene, mediates oncogenic properties in breast and other cancers. TAC1 expression facilitates the entry of breast cancer cells into bone marrow. The transcriptional repressor element 1-silencing transcription factor (REST) has been implicated in both oncogenic and tumor-suppressor functions. REST binds to the 5 untranslated region of the TAC1 promoter and suppresses its expression. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 27 publications
3
60
0
Order By: Relevance
“…Although in breast cancer the TAC1 gene coding for substance P was identified as a NRSF/REST target gene (Reddy et al, 2009), we could identify AKT2 important for cell proliferation and survival as a target of NRSF/ REST in SCLC. An siRNA-mediated knockdown of NRSF/REST expression in H128 enhanced transcription of the AKT2 and synaptophysin genes in H128.…”
Section: Discussionmentioning
confidence: 94%
“…Although in breast cancer the TAC1 gene coding for substance P was identified as a NRSF/REST target gene (Reddy et al, 2009), we could identify AKT2 important for cell proliferation and survival as a target of NRSF/ REST in SCLC. An siRNA-mediated knockdown of NRSF/REST expression in H128 enhanced transcription of the AKT2 and synaptophysin genes in H128.…”
Section: Discussionmentioning
confidence: 94%
“…In accordance with this, loss of REST function has been implicated in several human cancers, including breast, prostate, ovarian, colorectal, pancreatic, and small-cell lung cancers (1,6,9,15,19,35,51,56). In breast cancer cells, REST has been found to repress the oncogenic TAC1 gene, as well as cell proliferation and migration (39). These findings indicate that REST plays a pivotal role in suppressing cancer formation and may represent a potential therapeutic target of some human cancers.…”
mentioning
confidence: 81%
“…It was recently shown that, together with NFkB, REST represses TAC1 expression in mesenchymal stem cells. However, the level of REST decreases in breast cancer cells and inversely correlates with substance P production and an aggressive cellular phenotype (Reddy et al, 2009). …”
Section: Breast Cancermentioning
confidence: 99%